2020
DOI: 10.3991/ijet.v15i24.14017
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia-Assisted Learning in a Flipped Classroom: A Case Study of Autonomous Learning on EFL University Students

Abstract: This current study purposed to investigate the use of multimedia-assisted learning in a flipped classroom for fostering the students’ autonomous learning on EFL University. The students are encouraged to learn independently by having multimedia learning sources and they are also stimulated to find their difficulties in the learning process. Meanwhile, teacher and students are discussing the solution from the students’ difficulties during their independent learning in the classroom. The successful completion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 29 publications
0
30
0
2
Order By: Relevance
“…Besides, it was observed that the transfer of materials from the conventional face-to-face model to the computer-mediated format requires specialized expertise, time, and dedication (Cai et al, 2019). Moreover, the usage of efficient technology must be reviewed beforehand because this helps facilitate outside-class engagement amongst students (Aprianto & Purwati, 2020). These suggestions shared by Cai et al (2019) and Aprianto and Purwati (2020) demonstrate that there is still uncertainty among students when it comes to technology-enhanced learning (TEL).…”
Section: Flipped Classrooms: a Remedy To Achieve Inclusive Education?mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it was observed that the transfer of materials from the conventional face-to-face model to the computer-mediated format requires specialized expertise, time, and dedication (Cai et al, 2019). Moreover, the usage of efficient technology must be reviewed beforehand because this helps facilitate outside-class engagement amongst students (Aprianto & Purwati, 2020). These suggestions shared by Cai et al (2019) and Aprianto and Purwati (2020) demonstrate that there is still uncertainty among students when it comes to technology-enhanced learning (TEL).…”
Section: Flipped Classrooms: a Remedy To Achieve Inclusive Education?mentioning
confidence: 99%
“…Moreover, the usage of efficient technology must be reviewed beforehand because this helps facilitate outside-class engagement amongst students (Aprianto & Purwati, 2020). These suggestions shared by Cai et al (2019) and Aprianto and Purwati (2020) demonstrate that there is still uncertainty among students when it comes to technology-enhanced learning (TEL). The migration of materials from traditional face-to-face format to computer-mediated format is a process that requires specific skills, as well as a significant amount of time and effort…”
Section: Flipped Classrooms: a Remedy To Achieve Inclusive Education?mentioning
confidence: 99%
“…Innovative information technologies have been used in many studies for language learning [26,27,28,29]. In language learning, the most used technologies were corpus, online videos, websites, social networking, intelligent tutoring system, etc.…”
Section: Information Technology Assisted In Language Learningmentioning
confidence: 99%
“…Since then the FC has spread to a wide community of educational institutions and educators around the world, reaching out to higher education [6]. The FC as a pedagogical model requires the commitment and active participation of students in learning activities both before and in the classroom, all with the contribution of information and communication technologies [7]- [9].…”
Section: Introductionmentioning
confidence: 99%